ThunderKAT: The MeerKAT Large survey project for image-plane radio transients - Fender, R.; Woudt, P.; Armstrong, R.; Groot, P.; McBride, V.; Miller-Jones, James; Mooley, K.; Stappers, B.; Wijers, R.; Bietenholz, M.; Blyth, S.; Bottcher, M.; et al. (2016)
© Copyright owned by the author(s). ThunderKAT is the image-plane transients programme for MeerKAT. The goal as outlined in 2010, and still today, is to find, identify and understand high-energy astrophysical processes via their radio emission (often in concert with observations at other wavelengths). Through a comprehensive and complementary programme of surveying and monitoring Galactic synchrotron transients (across a range of compact accretors and a range of other explosive phenomena) and exploring distinct populations of extragalactic synchrotron transients (microquasars, supernovae and possibly yet unknown transient phenomena) - both from direct surveys and commensal observations - we will revolutionise our understanding of the dynamic and explosive transient radio sky. As well as performing targeted programmes of our own, we have made agreements with the other MeerKAT large survey projects (LSPs) that we will also search their data for transients. This commensal use of the other surveys, which remains one of our key programme goals in 2016, means that the combined MeerKAT LSPs will produce by far the largest GHz-frequency radio transient programme to date.